IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN IPS KELAS VII DI SMP LKIA PONTIANAK - Lingga, Metro; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the teacher's understanding of SOCIAL SCIENCE subjects in implementing the curriculum in junior high LKIA 2013 Pontianak Class VII. The research method used is descriptive qualitative research form. Data source this study is the head of the school, the teachers ' teacher. The results showed an understanding teacher teachers in understanding curriculum 2013 well enough alone with any approach towards learners wide and deep still less can be seen there are still some students who choose busy playing and not focus learn. For designing learning activities such as being able to make and teach in accordance with RPP made, able to execute very well learning activities, such as being able to describe the topics of discussion on subjects being information an interesting and easily understood by most learners, able to customize classes when learning activities are taking place, are able to evaluate the learning progress of students very well, such as implementing a written or oral test assessment, analyze the results of a study to determine the level of ketuntasan learning, can involve themselves to develop the potential of students and also was able to identify talent and interest the students very well, like knowing the learners interest in learning or not.Â Keywords: K13, Implementation and learning IPS